2020
DOI: 10.1039/d0ta07438a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cycling stability of high-voltage lithium metal batteries with a trifunctional electrolyte additive

Abstract: Carbonate-based electrolytes have been extensively employed in commercial Li-ion batteries, but they faces numerous interphasial stability challenges while supporting the high-voltage cathode chemistries and lithium metal anode, which result in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 34 publications
1
47
0
Order By: Relevance
“…Since the commercialization of the lithium-ion battery, its energy density and cycle life have been significantly improved and become an indispensable part of modern life. Compared with the rapid evolution of electrode materials, especially the cathode chemistries, the electrolyte composition has remained largely static, with lithium hexafluorophosphate (LiPF 6 ) dissolved in mixture of carbonates as the skeletal composition . This relative lack of activity has been mainly due to the success of the current electrolyte composition with well-balanced properties. However, there are still bottlenecks imposed by such traditional electrolyte, especially with the increase of working voltage of the battery .…”
Section: Does High Voltage Accelerate the Hydrolysis Of Lipf6?mentioning
confidence: 99%
“…Since the commercialization of the lithium-ion battery, its energy density and cycle life have been significantly improved and become an indispensable part of modern life. Compared with the rapid evolution of electrode materials, especially the cathode chemistries, the electrolyte composition has remained largely static, with lithium hexafluorophosphate (LiPF 6 ) dissolved in mixture of carbonates as the skeletal composition . This relative lack of activity has been mainly due to the success of the current electrolyte composition with well-balanced properties. However, there are still bottlenecks imposed by such traditional electrolyte, especially with the increase of working voltage of the battery .…”
Section: Does High Voltage Accelerate the Hydrolysis Of Lipf6?mentioning
confidence: 99%
“…[28][29][30] At cathode/electrolyte interface, the introduction of artificially inorganic/polymeric layers is a general and effective strategy to improve the stability. [17,31] For example, Choudhury et al reported lithium's semi-crystalline anionic polymer electrolyte to coat the cathode to improve cyclic stability of high-voltage oxide materials. [2] Although the aforementioned strategies show their advantages for improving the cyclic stability of anode/ cathode, they still cannot concurrently meet the high requirements of stable interfaces for both high oxidation cathode and reduction anode.…”
mentioning
confidence: 99%
“…The discharge capacity of LNMO in the baseline electrolyte drops dramatically after around 300 cycles, which is similar to our previous works showing the poor cycle stability of LNMO in an additive-free electrolyte. [16][17][18]21,35,37 Application of a 2 wt % 4TP additive prominently enhances the longterm cycle stability of the LNMO/Li cell, which achieves a capacity retention of 89% after 480 cycles at the current rate of 1C in comparison with that of only 26% achieved by without additive. It can be also found that the capacity retention of LNMO with 1 wt % 4TP additive is not as high as that of LNMO with 2 wt % 4TP, which might be due to the insufficient content of additive to form an integral CEI film.…”
Section: Resultsmentioning
confidence: 99%
“…In our recent work, a film-forming additive TTS has been demonstrated to effectively improve the capacity retention of LNMO/Li cell up to 92% from 48% after 500 cycles by generating a stable cathode/electrolyte interphase (CEI) film on the surface of LNMO. 16 However, in addition to the effect of additive, its price is also a concern. Therefore, it is of great significance to develop an efficient and economical electrolyte additive to achieve the industrial application of a high-voltage LNMO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation